Towards a model of chain-by-chain magnetization of a granular medium: a variant of magnetic diagnostics of chains of spheres - A. A. Sandulyak; D. A. Sandulyak; Yu. О. Gorpinenko; V. A. Ershova; A. V. Sandulyak (Российский технологический журнал, 2021)
In addition to information on the magnetic parameters of inhomogeneous magnetics, in particular, granular magnetics usually studied within the framework of the quasi-continuous medium model, it is of no less interest to obtain information from the standpoint of the model, when the object of study is the characteristic elements of an inhomogeneous magnetic. According to the well-proven model of selective magnetization of a granular medium, the elements that make up this medium are chains of granules – straight and sinuous, always manifesting themselves in the direction of its magnetization. They perform the function of conductor channels of the generated magnetic flux through the granular medium. As a result, it is a kind of branched «bundle» of conductor channels. For any of the chains of granules, for example, granules-balls of radius R, conceptually significant are the magnetic parameters of its conditional cores with radius r ≤ R, and these parameters, first of all, the magnetic permeability of quasi-continuous cores and magnetic induction in them, for different (in r) cores are variable, which requires appropriate magnetic diagnostics. To clarify the magnetic parameters of the conditional cores of a chain of granules-balls, as a physically self-sufficient element of a granular medium (i.e., in accordance with the model of chain-link magnetization of such a medium), it is practical to make measuring magnetic flux sensors in the core as circular sensors surrounding the contact point of granules-balls, however, not as traditional wire loops, but as circuits on thin printed circuit boards (with mounting holes) placed between adjacent balls. Based on the obtained data of the magnetic flux in cores of different radii r (r/R = 0.2–0.9) of a chain of spheres with a radius of R = 20 mm, the values of the magnetic induction B in them, as well as their magnetic permeability μ, were determined when the chain is magnetized in the solenoid by a field of strength from 4.8 to 54.5 kA/m. It is shown that with formal thickening of the cores, the values of B and μ decrease due to a decrease in the volume of the ferromagnet in the core, and for the limiting core (r/R → 1), i.e., for the chain as a whole, they correspond to the values of B and μ for a poly-ball backfill medium.